(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article investigates the features of the expression of traditional attitudes to life in the social and domestic proverbs, defined the essence of the concept of tradition. Traditional folk views on social life, observations of members of different social classes, which are passed from generation to generation, the determining characteristics of the national mentality of Ukrainians.